2009
DOI: 10.1016/j.jbiotec.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A portal for rhizobial genomes: RhizoGATE integrates a Sinorhizobium meliloti genome annotation update with postgenome data

Abstract: Sinorhizobium meliloti is a symbiotic soil bacterium of the alphaproteobacterial subdivision. Like other rhizobia, S. meliloti induces nitrogen-fixing root nodules on leguminous plants. This is an ecologically and economically important interaction, because plants engaged in symbiosis with rhizobia can grow without exogenous nitrogen fertilizers. The S. meliloti-Medicago truncatula (barrel medic) association is an important symbiosis model. The S. meliloti genome was published in 2001, and the Medicago truncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 49 publications
0
46
0
Order By: Relevance
“…These encode a periplasmic substrate-binding protein (CbtJ), a permease (CbtK), and an ATP-binding protein (CbtL) of an ABC-type transport system. As discussed below, these genes were reannotated btuF, btuC, and btuD in the current S. meliloti genome database (4). Based on our data and unpublished work (J. Cheng et al, submitted for publication), we have designated these genes the cobalt transporter genes cbtJ, cbtK, and cbtL, respectively, and we use these names throughout this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These encode a periplasmic substrate-binding protein (CbtJ), a permease (CbtK), and an ATP-binding protein (CbtL) of an ABC-type transport system. As discussed below, these genes were reannotated btuF, btuC, and btuD in the current S. meliloti genome database (4). Based on our data and unpublished work (J. Cheng et al, submitted for publication), we have designated these genes the cobalt transporter genes cbtJ, cbtK, and cbtL, respectively, and we use these names throughout this work.…”
Section: Resultsmentioning
confidence: 99%
“…In previous reports based on informatics, the smb20056, smb20057, and smb20058 genes were designated btuFCD genes encoding a vitamin B 12 transport system (4,69). In another report, on the basis of mRNA transcript nucleotide sequencing, Mao et al (39) suggested that a small, 180-nucleotide open reading frame (vbismb0078) is located in the 5Ј-UTR of cbtJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether increased transcription of this operon was responsible for enhanced CR staining, we interrupted the putative uxs1-SMb20463 operon by integration of pK19mob2ΩHMB-uxe (40) into uxe in wild-type S. meliloti and in the mucR mutant. Integration of pK19mob2ΩHMB has been shown to disrupt transcription due to a strong transcription terminator encoded by this plasmid (40).…”
Section: Significancementioning
confidence: 99%
“…79 Next to 6296 protein-coding genes, the annotation of S. meliloti 1021 includes 545 trans-sRNAs, 3028 asRNAs, and the positions of TSS defining the 5′-UTR of 2832 mRNAs, all discovered in previous studies. 23,39 Sequencing reads from the five Hfq and the two control (C) CoIP cDNA libraries were preprocessed and individually mapped to the S. meliloti 1021 genome using Segemehl with standard parameters.…”
Section: Identification Of Hfq-dependent Transcripts/featuresmentioning
confidence: 99%